Occurrence of Mycotoxins in Fish Feed and Its Effects: A Review - Mariana Oliveira; Vitor Vasconcelos (Toxins, 2020)
Plant-based ingredients have been successfully replacing fishmeal in finished fish feeds. However, using crops in feeds results in an increased risk of contamination by fungi and mycotoxins and a higher incidence of mycotoxicosis in fish. This might decrease aquaculture’s productivity as mycotoxicosis generally result in decreased body weight, growth impairment and higher rates of disease and mortality in fish. Additionally, some mycotoxins might accumulate in the fish musculature. As such, fish consumption might become another way for mycotoxins to enter the human food chain, threatening food security and public health as mycotoxins are important genotoxins, carcinogens and immunosuppressors to humans. In this work we aim to provide a review on the most important mycotoxins found in crops and in finished fish feed, i.e., aflatoxins, fumonisins, ochratoxins, trichothecenes and zearalenone. We present their effects on the health of fish and humans and their regulations in the European Union. Although work has been performed in mycotoxin research ever since the 1960s, a lot of information is still lacking regarding its effects. However, it is noticed that in order to use crops in aquafeed production, efforts should be made in order to monitor its contamination by mycotoxinogenic fungi and mycotoxins.